2019
DOI: 10.1002/adfm.201907379
|View full text |Cite
|
Sign up to set email alerts
|

Cation‐Exchange Synthesis of Highly Monodisperse PbS Quantum Dots from ZnS Nanorods for Efficient Infrared Solar Cells

Abstract: Infrared solar cells that utilize low-bandgap colloidal quantum dots (QDs) are promising devices to enhance the utilization of solar energy by expanding the harvested photons of common photovoltaics into the infrared region. However, the present technology for synthesis of PbS QDs cannot produce highly efficient infrared solar cells. Here, we develop a general synthesis framework for low-bandgap PbS QDs (0.65-1 eV) via cation-exchange from ZnS nanorods (NRs). First, ZnS NRs are converted to superlattices with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
107
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 89 publications
(125 citation statements)
references
References 45 publications
(15 reference statements)
1
107
0
Order By: Relevance
“… (C) Light absorption spectra of CQDs with different dot sizes. Adapted with permission from Xia et al. (2019) .…”
Section: Infrared Pbs Cqdsmentioning
confidence: 99%
See 1 more Smart Citation
“… (C) Light absorption spectra of CQDs with different dot sizes. Adapted with permission from Xia et al. (2019) .…”
Section: Infrared Pbs Cqdsmentioning
confidence: 99%
“…Other synthetic methods, such as biomineralization ( Spangler et al., 2016 ) and ion exchange, were also studied for the synthesis of CQDs. Xia et al. (2019) demonstrated that the CQDs could be synthesized from ZnS nanorods using a cation exchange approach and the resulted CQDs had a low infrared E g .…”
Section: Infrared Pbs Cqdsmentioning
confidence: 99%
“…As a result, the PbSe/PbS QD IR solar cells focusing on a bandgap of ≈0.95 eV produce a high V OC which is 1.46 times that of pristine PbSe QD devices due to the improved surface passivation. Furthermore, the PbSe/PbS QD devices demonstrate a much higher IR J SC compared to the previously reported PbS QD devices [ 1,3,4,8,9,20,21 ] due to the strong electronic coupling among adjacent QDs. Consequently, we achieved a high Si‐filtered PCE of 1.24% without any light trapping nanostructure.…”
Section: Introductionmentioning
confidence: 71%
“…Matching the absorption spectrum of cSi with the solar spectrum ( Figure a), the short‐wavelength infrared (IR) (>1100 nm) photons which occupy approximately 20% of the whole sun's power reaching the Earth's surface are unavailable for cSi solar cells due to its indirect large bandgap of ≈1.1 eV. [ 1,3 ] Thus, it is a promising avenue to harvest these high transmissible low energy photons (<1.1 eV) for breaking through the efficiency limitation. Theoretical calculation has predicted that up to 6% extra power points can be appended to the Si‐based solar cells via cascading IR solar cell to collect the photons beyond 1100 nm of sunlight.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation